Effectiveness of the Homeopathic Preparation Neurexan® Compared with that of Commonly used Valerian-Based Preparations for the Treatment of Nervousness/Restlessness – an Observational Study. (2009) - Hubner, Rainer; van Haselen, Robbert; Klein, Peter
Abstract : Mild anxieties, nervousness, and restlessness are common in the general population and are commonly treated by complementary and alternative medical (CAM) therapies. A prospective, nonrandomized, noninterventional, observational study, using conventional or CAM practices, was conducted in 49 German practices. Each practice could include up to 15 subjects treated with either the homeopathic preparation Neurexan ® or with combination formulations based on valerian extracts. There was no placebo group. Choice and doses of study therapies were at the respective physician's discretion. The planned treatment duration was 2 weeks. A total of 826 subjects were included in the study and 777 (553 Neurexan and 224 valerian) subjects were available for the final examination. Subjects receiving Neurexan tended to weigh less, to have fewer concomitant illnesses and slightly milder severity of nervousness/restlessness, and were likelier to be female than the subjects receiving valerian therapies. The summary score for nervousness/restlessness was reduced from 19.0 ± 6.1 at baseline to 7.4 ± 6.8 at the end of the observation period in the Neurexan group, a reduction of 11.5 ± 7.3 score units. In the valerian group, the summary score was reduced from 21.4 ± 6.0 to 12.6 ± 7.3, a reduction of 9.0 ± 6.6 score units. The changes from baseline and the differences between the groups were statistically significant. Similar significant differences in effects were seen on the subscores and on the subjects' assessments of effectiveness. Both study therapies were well tolerated. Neurexan appears to be an effective and well-tolerated alternative to valerian-based combination therapies for the treatment of nervousness/restlessness in subjects favorable towards a CAM-based therapy.